2020
DOI: 10.1002/ijc.33445
|View full text |Cite
|
Sign up to set email alerts
|

Associations of coffee and tea consumption with lung cancer risk

Abstract: Associations of coffee and tea consumption with lung cancer risk have been inconsistent, and most lung cancer cases investigated were smokers. Included in this study were over 1.1 million participants from 17 prospective cohorts. Cox regression analyses were conducted to estimate hazard ratios (HRs) and 95% confidence intervals (CIs). Potential effect modifications by sex, smoking, race, cancer subtype and coffee type were assessed. After a median 8.6 years of follow‐up, 20 280 incident lung cancer cases were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 41 publications
(83 reference statements)
0
13
0
Order By: Relevance
“…Lung cancer, prostate cancer, and bladder cancer were not correlated with coffee consumption in the present study. Several studies estimated the risk of these cancers [31][32][33][34]. For lung cancer, a prospective cohort study reported an increased risk of lung cancer associated with coffee consumption (hazard ratio (HR) = 1.30, 95% CI = 1.15-1.47) [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lung cancer, prostate cancer, and bladder cancer were not correlated with coffee consumption in the present study. Several studies estimated the risk of these cancers [31][32][33][34]. For lung cancer, a prospective cohort study reported an increased risk of lung cancer associated with coffee consumption (hazard ratio (HR) = 1.30, 95% CI = 1.15-1.47) [31].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies estimated the risk of these cancers [31][32][33][34]. For lung cancer, a prospective cohort study reported an increased risk of lung cancer associated with coffee consumption (hazard ratio (HR) = 1.30, 95% CI = 1.15-1.47) [31]. Another prospective cohort study also reported a higher risk of lung cancer associated with coffee consumption (HR = 1.18, 95% CI = 1.02-1.36) [32].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding smoking, the association between plant diet and COPD may be due, in part, to a residual confounding by cigarette smoking, which is a powerful risk factor. To minimize this possibility, multivariable models were adjusted with multiple time-varying measures of tobacco exposure; using this detailed control for smoking as time-dependent variable was able, for example, to reduce an age-adjusted relative risk of 4 for coffee consumption and lung cancer risk to a fully adjusted relative risk of 1.0 [ 32 ]. We also acknowledge that there is some misclassification of diet assessed by the food frequency questionnaire.…”
Section: Discussionmentioning
confidence: 99%
“…We provide a wealth of up- Cancer risk is significantly increased by 47% in the population with the highest category intake of coffee compared with that with the lowest category intake. Zhu, 2020 [137] 17 prospective cohort studies (1.1 million Pt and 20,280 Cc) Uninformed Higher consumption of coffee is associated with increased cancer risk.…”
Section: Discussionmentioning
confidence: 99%